Identyfikacja i zastosowanie kontekstu w uczeniu z nadzorem - Jakubczyc, Janina Anna (The Context Identification and Application in the Supervised Learning, 2006)
The context gives the ability to more adequate description, better understanding and generating more appropriate classifiers for multiply context in studied phenomena. The author has proposed context identification method in the learning example and the way in which this recurring context may be exploited.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1121, s. 44-52